Sorting Nexin 10 as a Key Regulator of Membrane Trafficking in Bone-Resorbing Osteoclasts: Lessons Learned From Osteopetrosis - Elson, Ari; Stein, Merle; Rabie, Grace; Barnea-Zohar, Maayan; Winograd-Katz, Sabina; Reuven, Nina; Shalev, Moran; Sekeres, Juraj; Kanaan, Moien; Tuckermann, Jan; Geiger, Benjamin (Frontiers in Cell and Developmental Biology, 2021)
Bone homeostasis is a complex, multi-step process that is based primarily on a tightly orchestrated interplay between bone formation and bone resorption, executed by osteoclasts, which degrade bone, and osteoblasts that build it. The essential physiological balance between these cells is maintained and regulated at multiple levels, ranging from cellular gene expression to endocrine signals, yet the underlying cellular and molecular mechanisms are still poorly understood. One approach for deciphering the mechanisms that regulate bone homeostasis is the characterization of relevant pathological states in which this balance is disturbed. In this article we describe one such “error of nature”, namely the development of acute osteopetrosis in humans that is caused by mutations in sorting nexin 10 (SNX10). We hypothesize that, by virtue of its roles in cellular membrane trafficking, SNX10 is a master regulator of the development, function, and fate of osteoclasts. In support of this proposal we describe the origin and spread of the original arginine-to-glutamine mutation at position 51 (R51Q) mutation in SNX10 in the Palestinian population in which it was identified. We further review recent studies, obtained in animal and cellular model systems, that document the roles of SNX10 in critical membrane sorting processes that take place during osteoclastogenesis, including the regulated fusion of precursor cells, trafficking of endosomes and lysosomes, assembly of the ruffled border, and adhesion to the bone matrix. Collectively, these studies document the key role of SNX10 in maintaining the fine balance between bone formation and degradation and in preserving bone homeostasis.